2021
DOI: 10.1017/s1368980021002469
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the policy process for the implementation of nutritional warning labels in Uruguay

Abstract: Objective: To analyse the process for the development and implementation of mandatory nutritional warning labels in Uruguay, in order to inform future nutrition policy making and strategic engagement by public health actors. Design: The study design drew on policy analysis methodology and case study research methodology. Two main sources of information were selected and analysed for the current study: eighteen official documents from the Uruguayan government and 259 news reports, publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The introduction of comprehensive packaging regulations cannot be expected to be an easy task. Efforts by governments to introduce such regulations have faced fierce opposition globally, mainly in the form of opposition from the food industry and trade challenges (Ares, Antúnez, Cabrerar, & Thow, 2021;Dorlach & Mertenskötter, 2020;Julia & Hercberg, 2016;Mulligan et al, 2021;Vandenbrink et al, 2020). In particular, research has shown that the food industry engages in corporate political activity to promote deregulation (Ares, Antúnez, Cabrerar, & Thow, 2021;Julia & Hercberg, 2016;Mialon et al, 2020;Vandenbrink et al, 2020).…”
Section: Challenges For the Introduction Of Comprehensive Packaging Regulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of comprehensive packaging regulations cannot be expected to be an easy task. Efforts by governments to introduce such regulations have faced fierce opposition globally, mainly in the form of opposition from the food industry and trade challenges (Ares, Antúnez, Cabrerar, & Thow, 2021;Dorlach & Mertenskötter, 2020;Julia & Hercberg, 2016;Mulligan et al, 2021;Vandenbrink et al, 2020). In particular, research has shown that the food industry engages in corporate political activity to promote deregulation (Ares, Antúnez, Cabrerar, & Thow, 2021;Julia & Hercberg, 2016;Mialon et al, 2020;Vandenbrink et al, 2020).…”
Section: Challenges For the Introduction Of Comprehensive Packaging Regulationsmentioning
confidence: 99%
“…Efforts by governments to introduce such regulations have faced fierce opposition globally, mainly in the form of opposition from the food industry and trade challenges (Ares, Antúnez, Cabrerar, & Thow, 2021;Dorlach & Mertenskötter, 2020;Julia & Hercberg, 2016;Mulligan et al, 2021;Vandenbrink et al, 2020). In particular, research has shown that the food industry engages in corporate political activity to promote deregulation (Ares, Antúnez, Cabrerar, & Thow, 2021;Julia & Hercberg, 2016;Mialon et al, 2020;Vandenbrink et al, 2020). The arguments of the food industry mainly rely on making consumers responsible for making healthy food choices and stressing the potential negative effect of the regulations in terms of costs required for implementation and their potential negative effects on sales (Ares, Antúnez, Cabrerar, & Thow, 2021;Mialon et al, 2020).…”
Section: Challenges For the Introduction Of Comprehensive Packaging Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…FoP labelling includes simplified information about nutritional content or health aspects of foods, and they are displayed on the front of the package to assist consumers make healthier food choices during their quick decision-making shopping process ( 16 ). In Chile, a FoP octagonal warning label stating “high-in-sugar” is mandatory for food products exceeding defined sugar content thresholds ( 17 ), and this same format has been implemented in Peru ( 18 ) and Uruguay ( 19 ) and approved to be implemented in Mexico ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional warnings have recently emerged as a FOP nutrition labelling scheme to discourage consumption of foods with excessive content of nutrients associated with non-communicable diseases (NCDs) 14 . This FOP nutrition labelling scheme has been implemented as black octagons highlighting pre-packaged foods with excessive content of calories, sugar, fat, saturated fat and sodium, in several Latin American countries (Chile, Peru, Uruguay, and Mexico) 15,16,17,18 . An increasing body of evidence shows that nutritional warnings are easy to understand, facilitate the identification of foods with excessive content of nutrients associated with NCDs, and discourage consumers from choosing them 19,20 .…”
Section: Introductionmentioning
confidence: 99%